Insomnia and Associated Factors among Anaesthetists in Hong Kong. Issue 6 (November 2013) - Lee, K. Y.; Chen, P. P.; Tse, L. A.
The primary objective of this survey was to investigate the prevalence of insomnia among anaesthetists in Hong Kong. The use of sleeping aids, factors associated with insomnia and the effect of insomnia on work performance were also studied. We surveyed all locally registered anaesthesia specialists and trainees by post. The response rate was 50%. We found that the prevalence of insomnia among the respondents was 22.4% (95% confidence interval 16.7 to 28.1%). Insomnia was positively associated with the number of on-call shifts per month ( P =0.002) and poor relationship with supervisors ( P =0.009). Alcohol was the most frequently used aid to assist sleep, followed by Zolpidem. The majority of respondents using sleeping medication obtained the drug over-the-counter, by self-prescription or prescription by colleagues. Only 4.3% (95% confidence interval 0 to 10.2%) of respondents suffering from insomnia had formal medical consultation for sleep disturbance. Insomnia was associated with increased subjective sleepiness at work ( P =0.007) and subjective decline in work performance during both daytime ( P <0.001) and night-time ( P <0.001). However, it was not associated with the tendency to fall asleep at work. The results of this survey suggest that insomnia is a common problem among the anaesthetists of Hong Kong. By restricting the amount of on-call duty and improving relationships with supervisors, the prevalence of insomnia may be reduced and the quality of patient care improved.